Waiting for the Web: How Screen Color Affects Time Perception - Gorn, Gerald J.; Chattopadhyay, Amitava; Sengupta, Jaideep; Tripathi, Shashank (Journal of Marketing Research, 2004)
The authors investigate the link between the color of a Web page's background screen while the page is downloading and the perceived quickness of the download. They draw on research that supports links between color and feelings of relaxation and between feelings of relaxation and time perception. The authors predict that the background screen color influences how quickly a page is perceived to download and that feelings of relaxation mediate this influence. In a series of experiments, they manipulate the hue, value, and chroma dimensions of the color to induce more or less relaxed feeling states. The findings suggest that for each dimension, colors that induce more relaxed feeling states lead to greater perceived quickness. The authors provide triangulating evidence with an alternative manipulation: the number of times subjects wait for a download. As does color, this also leads to variation in levels of relaxation and perceived quickness. A final experiment reveals that color not only affects perceived download quickness but also has consequences for users' evaluations of the Web site and their likelihood of recommending it to others.